The Development of Katsina State Civil Service, 1987–2022 - Wycliff, Samuel; Katsina, Hadiza Sani (NIU Journal of Humanities, 2023)
Katsina State was known to be home of heritage and hospitality before and since its creation from the defunct Kaduna State on 23 rd September, 1987. In view of that, this paper through the historical method of data collection and employment of primary and secondary source materials examines the development of Katina State Civil Service from the creation of the state until 2022 when it turned 35 years. The paper argues that, since the establishment of Civil Service in 1987, Katsina State has experienced major landmarks in its transformation to its contemporary phases. Notably, key factors in the transformation of the state included among other things the deployment of civil servants from the defunct Kaduna State and different parts of Nigeria to the new state, effective implementation of government policies and programs, employment opportunities through the establishment of Federal and State and Local Government departments ministries, parastatals, and agencies, and then the general human resource development through in-service, training and re-training of the civil servants. To this end, the paper, concludes that, there is no development without limitations and the development of Katsina State Civil Service was no exception. Such as politicization, corruption, nepotism, favoritism, selective promotion, ghost workers, partisan politics, godfathers, disregard for Civil Services Rules and Regulations and the Civil Service Commission all of which hindered effective service delivery in the state. Keywords: Civil Service, Development, Katsina State, Prospects, Challenges